INCREASING ENERGY EFFICIENCY IN AEROSPACE INDUSTRY THROUGH EMPLOYEES’ ENERGY AWARENESS AND KNOWLEDGE - Amar Hisham Jaaffar; Say Keat Ooi (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Typically, the aerospace industry used numerous non-renewable resources, like titanium and alloy. Additionally, the design of the flight’s materials also involves the use of fossil fuel. In fact, the aerospace industry is strongly related with air pollution. Nonetheless, energy is important in improving social and economic and its increasing demand related to increase in industrialization, population and has improved peopleâ€™s lifestyles. Hence, this study aims to examine the relationships between employeesâ€™ energy awareness, knowledge and energy efficiency in the aerospace industry in Malaysia. Based on the data collected from 210 employees in the aerospace industry, findings show that energy awareness and knowledge of the employees are strongly influencing energy efficiency practices of the organisation. As such, this paper sheds some light on organisational energy efficiency practices and provides valuable insights on how businesses can capitalise on employeesâ€™ energy awareness and knowledge in enhancing energy efficiency practices leading towards sustainable development.